Evidence for Rosa damascena efficacy in mental disorders in preclinical animal studies and clinical trials: A systematic review. (2nd June 2022) - Mohamadi, Neda; Pourkorrani, Mohammad Hossein Sotoudeh; Langarizadeh, Mohammad Amin; Ranjbartavakoli, Marziye; Sharififar, Fariba; Asgary, Sedigheh
Abstract: The aim of this systematic review was to identify animal preclinical studies and randomized controlled trials that looked at the effects of R. damascena in any form on different mental diseases. Up to September 2021, the online databases of PubMed, Scopus, Embase, Web of Science, and Cochrane trials, as well as SID and MagIran, were searched. This study included 10 animal studies. Except for one research, the rest of the studies confirmed the positive effects of the plant in treatment of mental disorders. A total of 38 studies met the criteria for inclusion. Individuals who have encountered various sorts of mental problems, such as anxiety, sleep disturbance, and depressive disorder, were studied. R. damascena essential oil (EO), essence, extract, and dried plant were used in aromatherapy and oral administration. A decrease in sympathetic nervous system activity, induction of neurotransmitters, induction of nerve growth factors by neurogenesis and synaptogenesis mechanisms, a decrease in prolactin and an increase in noradrenaline, estradiol, and progesterone secretion are some of the mechanisms of action. In general, R. damascena is an effective herb for the treatment of mental disorders. However, further research timing and duration of intervention are needed to extrapolate the findings.